2023
DOI: 10.21203/rs.3.rs-2936074/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Bitter Orange Blossom Distillate on Anxiety and Sleep Disorder in Mothers with Infants Admitted to Neonatal Intensive Care unit: A Randomized Controlled Clinical Trial

Abstract: Background:Mothers of neonates admitted to the intensive care unit are prone to sleep disorders due to stress and anxiety. Some herbs have anti-anxiety and sedative properties.The aim of this study was to investigate the effect of bitter orange blossom distillate on anxiety and sleep disorder in mothers with infants admitted to neonatal intensive care unit. Methods:This randomized controlled clinical trial was conducted in 2021on 60 mothers with NICU-admitted infants in one of the medical teaching centers affi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Thus, the highest amount of essential oil extracted from lemon balm is typically obtained by this method, in which the desired plant is directly placed in a distillation flask inside water, and then about two-thirds of its volume is filled with water, and heated. The produced water vapors contain essential molecules, which are liquefied after traveling through refrigerant pipes, and collected in the receiving container [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the highest amount of essential oil extracted from lemon balm is typically obtained by this method, in which the desired plant is directly placed in a distillation flask inside water, and then about two-thirds of its volume is filled with water, and heated. The produced water vapors contain essential molecules, which are liquefied after traveling through refrigerant pipes, and collected in the receiving container [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it has been demonstrated that using C. aurantium essential oil for aromatherapy in pregnant women with sleep disorders could remarkably improve their sleep quality(Mohammadi et al, 2022). Furthermore, a recent clinical trial reported that the administration of C. aurantium blossom distillate to mothers with neonatal intensive care unitadmitted infants reduced sleep disorder scores in comparison with the mothers in the placebo group(Dehghan et al, 2023).Finally, both in vitro and in vivo investigations have indicated that C. aurantium extracts and essential oils can increase sleep duration, reduce sleep latency, and mitigate sleep disorders in several laboratory methods. Clinical research with C. aurantium essential oil has further confirmed its effectiveness in improving sleep quality.…”
mentioning
confidence: 99%